A systematic literature review: how do we support students to become numerate? - Viona Adelia; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Institute of Advanced Engineering and Science, 2024)
Numeracy is the essential skill for life situations that involve mathematical elements and developing students’ numeracy skills is considered a primary goal of mathematics education. Despite its importance, numeracy can be challenging to teach, and it is not a guaranteed result of classroom mathematics learning. Through a systematic literature review, 35 studies about supporting students in becoming numerate in classrooms or courses are explored, this literature review also explained abilities included as numeracy, recommendations for teachers are given as well as some examples was given, also opportunities and directions for further research are identified, including guidelines for enhancing students’ numeracy competence.